Intelligent Finance: The Role of Artificial Intelligence in Profit Optimization in Peru - Rojas-Plasencia, Karina Milagros (2025)
The global adoption of artificial intelligence (AI) continues to expand, with 94% of business leaders recognizing its importance and 56% implementing it in customer service. However, in Latin America—and particularly in Peru—its adoption remains incipient. The objective of this research was to analyze the role of artificial intelligence in decision-making aimed at profitability in Peruvian companies within the financial sector during 2023. The applied method was basic, with a descriptive level, qualitative approach, and non-experimental design. The population consisted of 64 companies in the financial sector, from which a purposive sample of 9 was selected. A semi-structured interview was used as the data collection technique. The results indicate that artificial intelligence plays a fundamental role in data optimization and analysis, process automation, and trend identification, which strengthens the predictive and operational capacity of organizations. It is concluded that the use of AI significantly contributes to efficient information management, enhances the ability to anticipate market behavior, and optimizes key processes, all of which positively impact strategic decision-making aimed at improving business profitability.